Aspirin triggers previously undescribed bioactive eicosanoids by human endothelial cell-leukocyte interactions. - Clària, J (1995)
Aspirin [acetylsalicylic acid (ASA)], along with its analgesic-antipyretic uses, is now also being considered for cardiovascular protection and treatments in cancer and human immunodeficiency virus infection. Although many of ASA's pharmacological actions are related to its ability to inhibit prostaglandin and thromboxane biosynthesis, some of its beneficial therapeutic effects are not completely understood. Here, ASA triggered transcellular biosynthesis of a previously unrecognized class of eicosanoids during coincubations of human umbilical vein endothelial cells (HUVEC) and neutrophils [polymorphonuclear leukocytes (PMN)]. These eicosanoids were generated with ASA but not by indomethacin, salicylate, or dexamethasone. Formation was enhanced by cytokines (interleukin 1 beta) that induced the appearance of prostaglandin G/H synthase 2 (PGHS-2) but not 15-lipoxygenase, which initiates their biosynthesis from arachidonic acid in HUVEC. Costimulation of HUVEC/PMN by either thrombin plus the chemotactic peptide fMet-Leu-Phe or phorbol 12-myristate 13-acetate or ionophore A23187 leads to the production of these eicosanoids from endogenous sources. Four of these eicosanoids were also produced when PMN were exposed to 15R-HETE [(15R)-15-hydroxy-5,8,11-cis-13-trans-eicosatetraenoic acid] and an agonist. Physical methods showed that the class consists of four tetraene-containing products from arachidonic acid that proved to be 15R-epimers of lipoxins. Two of these compounds (III and IV) were potent inhibitors of leukotriene B4-mediated PMN adhesion to HUVEC, with compound IV [(5S,6R,15R)-5,6,15-trihydroxy-7,9,13-trans-11-cis-eicosatetraenoi c acid; 15-epilipoxin A4] active in the nanomolar range. These results demonstrate that ASA evokes a unique class of eicosanoids formed by acetylated PGHS-2 and 5-lipoxygenase interactions, which may contribute to the therapeutic impact of this drug. Moreover, they provide an example of a drug's ability to pirate endogenous biosynthetic mechanisms to trigger new mediators.